2007
DOI: 10.1007/s10508-007-9245-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Sexual Arousal in Men: A Focus Group Study

Abstract: The goal of this study was to improve our understanding of men's sexual response and its components as well as the factors or types of situations that men describe as facilitating or interfering with sexual arousal. Six focus groups, involving 50 mostly white, heterosexual men (M age = 35.2 years; range, 18-70), were conducted. As it was previously found in women (Graham, Sanders, Milhausen, & McBride, Archives of Sexual Behavior, 33, 527-538, 2004), men described a wide range of physical (genital as well as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 40 publications
10
74
0
Order By: Relevance
“…At nongender/sexed, 12 sexual attractions are based on other factors, like power, intelligence, humor, kindness, etc. (e.g., Janssen, McBride, Yarber, Hill, & Butler, 2008). There are various ways that attractions may be nongender/sexed: for example, gender/sex may be irrelevant to a person's attractions or to the person they are with.…”
Section: Sexual Configurationmentioning
confidence: 99%
“…At nongender/sexed, 12 sexual attractions are based on other factors, like power, intelligence, humor, kindness, etc. (e.g., Janssen, McBride, Yarber, Hill, & Butler, 2008). There are various ways that attractions may be nongender/sexed: for example, gender/sex may be irrelevant to a person's attractions or to the person they are with.…”
Section: Sexual Configurationmentioning
confidence: 99%
“…In a study focusing on the relationship between sexual desire and relationship functioning among community couples, Brezsnyak and Whisman (2004) found that higher levels of marital satisfaction predicted higher levels of sexual desire for husbands as well as for wives. Finally, many men, like women, noted that the context for the sexual interaction (e.g., having sex in a place where they could be seen or heard) and alcohol use could inhibit or enhance their arousal (Janssen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the SIS/SES questionnaire encompasses a number of these factors (e.g., elements of setting, partner arousal, partner attractiveness), others are not represented. The recent focus group study of men (Janssen et al, 2007) highlighted that partner characteristics and relationship dynamics may be particularly important influences on 7 men's sexual arousal. A scale validated for use with both men and women that would assess propensity for sexual arousal in response to a broader range of stimuli and sexual situations could be useful for future research on gender differences and similarities.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who advocated this amalgamation [12] based their recommendations on a large body of research suggesting that the separation may have been artificial. In addition to the increased rejection of a linear model of sexual arousal [8,9], a high comorbidity of disorders of desire and arousal was demonstrated in both men and women [13,14]. However, the response to this alteration was not unanimously positive.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, diagnostic categories of female sexual interest as described in the DSM IV 1994 [4] were based on the model of human sexual response proposed by Masters and Johnson [5], and further developed by Kaplan [6]. However, recent research has put into question the validity of that model; both the strict distinction between different phases of arousal and the linear model of sexual response were found to inadequately explain sexual behavior, particularly in women [7][8][9]. This has in turn led to several proposed changes in sexual dysfunction diagnostic criteria [1,10].…”
Section: Introductionmentioning
confidence: 99%